Identifikasi Indikasi Geografis Pada Tenunan Sapu Lu’e Lawo dan Perlindungan Hukum sebagai Hak Kekayaan Intelektual Komunal pada Masyarakat Adat Bajawa - Geme, Maria Theresia; Lay, Benediktus Peter; Rade, Stefanus Don (UNES Law Review, 2023)
Sapu Lu'e Lawo is a set of woven traditional clothes for men and women in the Bajawa indigenous community. This weave has Geographical Indication characteristics as one of the communal intellectual property. Geographical Indication is a sign indicating the area of origin of an item and or product which due to geographical environmental factors including natural factors, human factors, or a combination of both factors gives a certain reputation, quality, and characteristics to the goods and/or products produced. The main problem of this research is how the geographical indication of the Lu'e Lawo broom weave and how the form of legal protection. This type of research is Sociological Jurisprudence that relies on document studies as well as empirical studies through observation methods and in-depth interviews with weavers and leaders. The results of the study found that there is an element of geographical indication in the weaving of Sapu Lu'e Lawo which is a combination of natural factors, human factors and a combination of both factors contained in the shape, motif, color, material and value message in the ritual of making it, so it requires legal protection in accordance with applicable laws and regulations. The conclusion is that Sapu Lu'e Lawo is a set of woven traditional clothing in the Bajawa customary law community that contains the quality, characteristics and reputation as a geographical indication that must be protected. It is recommended that the local government make policies that facilitate weavers' access to the availability of natural materials such as encouraging the expansion of new plantations to support the economy as well as preserving the living values of the Bajawa indigenous people.